Mr-Proadm Elevation Upon Icu Admission Predicts the Outcome of Septic Patients and is Correlated with Upcoming Fluid Overload. Issue 4 (October 2017) - Charles, Pierre-Emmanuel; Péju, Edwige; Dantec, Allyriane; Bruyère, Rémi; Meunier-Beillard, Nicolas; Dargent, Auguste; Prin, Sébastien; Wilson, Darius; Quenot, Jean-Pierre
ABSTRACT: Background: Among septic patients admitted to the intensive care unit (ICU), early recognition of those with the highest risk of death is of paramount importance. We evaluated the prognostic value of Procalcitonin (PCT), mid regional-proadrenomedullin (MR-proADM), copeptine and CT-proendothelin 1 (CT-ProET 1) concentrations. Methods: This was a prospective cohort study, which included 173 septic patient admitted to one ICU. Blood samples for biomarker measurements were obtained upon admission and on day 5. The predictive value of each biomarker regarding the risk of death at day 28 was assessed. The fluid balance was evaluated from admission to day 5. Results: All cause ICU mortality was 36.4%. All the biomarkers except CT-ProET-1 were significantly more elevated in the non-survivors than in the survivors upon day 1. This was especially true for MR-proADM (8.6 [5.9] vs. 4.4 [3.9] nmol/L; P < 0.0001) and for the CT-proET-1/MR-proADM ratio (52.9 [22.4] vs. 31.3 [26.6] arbitrary units; P < 0.0001). The best AUROCC values on day 1 were obtained with MR-ProADM and the CT-proET-1/MR-proADM ratio as well (0.75 [0.67–0.85] and 0.82 [0.75–0.89]; 95% CI, respectively). An improved accuracy was achieved on day 5. Moreover, MR-ProADM baseline levels and fluid balance over the 5-day period following ICU admission were strongly correlated (Rho = 0.41; P < 0.001). Conclusions: In patients admitted to the ICU with sepsis, MR-ProADM on admission was the best predictor of short-term clinical outcome if compared with others. This could be related to its ability to predict fluid sequestration. Abstract : Supplemental Digital Content is available in the text